Logistics System of Waste Management at the Mining Enterprises - MOCHALOVA, Lyudmila; SOKOLOVA, Olga; YURAK, Vera (Journal of Environmental Management and Tourism; Vol 10 No 1 (2019): JEMT Volume X Issue 1(33) Spring 2019, 2019)
The article considers the solutions related to the formation and use of production and consumption wastes at the enterprises of the mineral resources complex. Particular attention is paid to production waste in the form of solid mineral waste (man-made mineral deposits), which, on the one hand, represents a secondary mineral resource base, on the other hand - has a significant negative impact on various elements of the environment. The research aim is to form a logistics system of waste management at the enterprises of the mineral resources complex. The scientific novelty lies in the application of logistic principles, approaches and methods to the sphere of production and consumer waste management during the formation of a large amount of production waste. The article substantiates the importance of the formation and functioning of a logistics system of waste management at enterprises of the mineral resources complex. This logistic system can increase the level of organizational security and economic efficiency of managing production and consumption waste and thereby mitigate the environmental and economic problems of these enterprises.